MicroRNA-942 mediates hepatic stellate cell activation by regulating BAMBI expression in human liver fibrosis - Tao, Le; Nwosu, Zeribe C. (Archives of toxicology, 2018)
MicroRNA (miRNA)-mediated gene regulation contributes to liver pathophysiology, including hepatic stellate cell (HSC) activation and fibrosis progression. Here, we investigated the role of miR-942 in human liver fibrosis. The expression of miR-942, HSC activation markers, transforming growth factor-beta pseudoreceptor BMP and activin membrane-bound inhibitor (BAMBI), as well as collagen deposition, were investigated in 100 liver specimens from patients with varying degree of hepatitis B virus (HBV)-related fibrosis. Human primary HSCs and the immortalized cell line (LX2 cells) were used for functional studies. We found that miR-942 expression was upregulated in activated HSCs and correlated inversely with BAMBI expression in liver fibrosis progression. Transforming growth factor beta (TGF-β) and lipopolyssacharide (LPS), two major drivers of liver fibrosis and inflammation, induce miR-942 expression in HSCs via Smad2/3 respective NF-κB/p50 binding to the miR-942 promoter. Mechanistically, the induced miR-942 degrades BAMBI mRNA in HSCs, thereby sensitizing the cells for fibrogenic TGF-β signaling and also partly mediates LPS-induced proinflammatory HSC fate. In conclusion, the TGF-β and LPS-induced miR-942 mediates HSC activation through downregulation of BAMBI in human liver fibrosis. Our study provides new insights on the molecular mechanism of HSC activation and fibrosis.